3D intra-stacked CoO/carbon nanocomposites welded by Ag nanoparticles for high-capacity, reversible lithium storage1. Issue 23 (21st June 2015) - Chae, Changju; Kim, Ki Woong; Kim, Sue Jin; Lee, Daehee; Jo, Yejin; Yun, Young Jun; Moon, Jooho; Choi, Youngmin; Lee, Sun Sook; Choi, Sungho; Jeong, Sunho
<x xml:space="preserve">Abstract</x> We demonstrate 3D intra-stacked CoO/carbon nanocomposites welded by Ag nanoparticles with a capacity of 770 mA h g−1 at a current density of 2 A g−1, by reducing efficiently the irreversible capacity loss.